DETERMINING THE FACTORS AFFECTING THE STUDYING STRATEGY OF ENGINEERING STUDENTS USING TEXTBOOK - (:unkn) unknown (IATED-INT ASSOC TECHNOLOGY EDUCATION A& DEVELOPMENT, 2014)
This study reports the results of a study which explored the studying strategy using textbook of mechanical engineering students in Marmara University - Turkey. Students have answered the question What motivates you to read and study the course textbook?. Using qualitative methods, answers are analyzed and results are interpreted considering age, sex and achievement level. Even though it is recommended students to read their engineering textbooks thoroughly to gain a complete understanding of the subject, it is seen over the years that students generally do not give importance to reading. Also, some lectures that are full of theoretical concepts and zero real-world examples can get boring. So it is believed that it will be useful to determine what attracts students to read the course textbook. Findings reveal similar patterns in the studying strategy between students. The study suggest that engineering students in Marmara University - Turkey could benefit from reading assignments, enabling them to acquire the information they need to function effectively and efficiently in their future.
Keywords: Engineering students; textbook; studying strategy